Achieving excellent strength-ductility combination in an Inconel 625 superalloy via short-term stress-aging treatment. (1st July 2023) - Liu, Xudong; Fan, Jiangkun; Jiao, Dian; Tang, Bin; Kou, Hongchao; Sha, Gang; Li, Jinshan
Abstract: In this work, nanoscale δ phases and multiple deformation mechanisms were introduced into an Inconel 625 superalloy via short-term stress-aging treatment (SAT). The efficiency of SAT is about 10 times that of the conventional aging method. The SAT alloy, with superior yield strength (YS) (about 779.6 MPa) and elongation (EL) (about 53.8%), is better than all Inconel 625 superalloys reported in the past 10 years, including additive manufacturing and forging alloys. The high YS is caused by the blocking effect of nanoscale δ phases and Lomer-Cottrell (L-C) locks. Transmission electron microscopy observations at different strains indicate that the synergetic effect of l -C locks, dislocation slip, and twinning is responsible for the improvement of work hardening ability in the latter half of tensile deformation. The results can provide new insights for improving the mechanical properties of Ni-based superalloys. Graphical abstract: Image, graphical abstract